4CPS-184 What is the additionnal value of pharmaceutical interventions on [123i]-metaiodobenzylguanidine scintigraphy?. Issue 1 (23rd March 2023) - Chaïb, S; Flaus, A; Meguennani, M; Levigoureux, E; Bolot, C; Janier, M; Breant, V
Abstract : Background and Importance: [ 123 I]-metaiodobenzylguanidine (mIBG) scintigraphy is a tool to assess cardiac sympathetic innervation. It is used to discriminate parkinsonian syndromes. However, many drugs are known to interfere with this radiopharmaceutical that can lead to false results 1 Aim and Objectives: The aim of this study was to try to assess the impact of stopping interfering drugs with [ 123 I]-mIBG in a retrospective study before the recent introduction of pharmaceutical interviews in a nuclear medicine department. Material and Methods: A retrospective study from 01/01/2010 to 31/03/2022 was conducted to find out if a drug interaction could explain diagnostic mismatches between a [ 123 I]-Ioflupane and [ 123 I]-mIBG scintigraphies, focusing on the neurological indication i.e. the differential diagnosis of Parkinson's disease. On the nuclear medicine software, a search of all the patients who had both a [ 123 I]-Ioflupane and a [ 123 I]mIBG scan 2010 and June 2022 was performed. Each patient's chart is analysed and the diagnosis is collected. Results: 81 patients underwent [ 123 I]-mIBG imaging for the differential diagnosis of neurodegenerative disease and among them 42 had non-contributory [ 123 I]-Ioflupane imaging (51.9%). A divergent diagnosis between [ 123 I]-mIBG and [ 123 I]-Ioflupane was found in 31% of cases, representing 13 patients. A drug interaction could explain this medical interpretation mismatch in 2 patients (15.4%). Concerning the latter, drugs involved were calcium channel blockers. No abnormality of the sympathetic innervation was found whereas the [ 123 I]-Ioflupane scintigraphy found an abnormality of the dopaminergic transmission. These results may complement existing data suggesting that calcium channel blockers interfered in cardiac [ 123 I]-mIBG imaging through increased sympathetic activity 2 . Conclusion and Relevance: There is a great medical interest in continuing pharmaceutical interviews because drug interactions can lead to non-contributory or unconclusive examinations. In addition, setting up a clinical trial by re-examining these two patients but temporarily stopping the drugs potentially involved could be very interesting. Indeed, this work demonstrates the complexity of assessing the impact of pharmaceutical interventions. Moreover, this process should be evaluated for other categories of radiopharmaceuticals. References and/or Acknowledgements: 1. Emilio B, Francesco G, Cumali A., et al . 131I/123I-metaiodobenzylguanidine (mIBG) scintigraphy: procedure guidelines for tumour imaging. Eur J Nucl Med Mol Imaging . 2010 Dec;37 (12):2436–46. 2. A Stefanelli, G Treglia, I Bruno, et al. Pharmacological interference with 123I-metaiodobenzylguanidine: A limitation to developing cardiac innervation imaging in clinical practice? European Review for Medical and Pharmacological Sciences . 2013 May; 17 (10):1326–33 Conflict of Interest: No conflict of interest